Antimicrobial and anti-inflammatory compounds from a marine fungus Pleosporales sp. Issue 45 (4th November 2015) - Chen, Chao Jun; Zhou, Yi Qin; Liu, Xian Xian; Zhang, Wen Jing; Hu, Sha Sha; Lin, Li Ping; Huo, Guang Ming; Jiao, Rui Hua; Tan, Ren Xiang; Ge, Hui Ming
Graphical abstract: Abstract: Seven new compounds, pleosporallins A–G (1 –7 ), were isolated from Pleosporales sp., a fungus derived from a marine alga Enteromorpha clathrata . The structures of these compounds were elucidated by an extensive analysis of NMR, MS, CD spectra, and single crystal X-ray diffraction. Compounds 4 and 5 showed antimicrobial activity with their MIC values of 9.48 μg/ml and 7.44 μg/ml against Clavibacter michiganense subsp. Sepedonicus and Candida albicans, respectively. Compounds 1 –3 exhibited moderate inhibitory activities against the lipopolysaccharide (LPS)-induced intracellular IL-6 production of murine macrophage cell line RAW264.7.